The Columbia Companion to modern East Asian literature - Mostow, Joshua S., 1957- (Columbia University Press, 2003)
This extraordinary one-volume guide to the modern literatures of China, Japan, and Korea is the definitive reference work on the subject in the English language. With more than one hundred articles that show how a host of authors and literary movements have contributed to the general literary development of their respective countries, this companion is an essential starting point for the study of East Asian literatures. Comprehensive thematic essays introduce each geographical section with historical overviews and surveys of persistent themes in the literature examined, including nationalism, gender, family relations, and sexuality. Following the thematic essays are the individual entries: over forty for China, over fifty for Japan, and almost thirty for Korea, featuring everything from detailed analyses of the works of Tanizaki Jun'ichiro and Murakami Haruki, to far-ranging explorations of avant-garde fiction in China and postwar novels in Korea.